A University-Based Literacy Service-Learning Program for Youthful Offenders on Probation: A Preliminary Study of the Program's Development, Implementation and Feasibility. Issue 3 (3rd July 2019) - Hirschinger-Blank, Nancy; Staulters, Mimi; Sharma, Suniti; O'Neill Hajduk, Megan; Toler, Roselyn
Abstract: This article reports on the development, implementation and feasibility of a mid-Atlantic university-community service-learning literacy program for youth on probation. Undergraduate teacher candidates served as literacy instructors for the youth. We focus on benefits and administrative challenges of developing and implementing a preliminary service-learning program for probated youth living in the community. We analyzed focus group data collected from special education undergraduate instructors, interview data collected from probated youth and their case managers, pre-post literacy assessments administered to the youth, the youths' court files and data maintained by the community-based agency. We conclude that our model of a university-community literacy partnership has the potential to raise reading performance of youth, motivation, and promote prosocial behaviors. Addressing the educational needs of youth on probation, however, is complex and multifaceted. We find that success requires consistent communication among all stakeholders, adequate funding for leadership, organization and curricula, and ongoing assessment and evaluation.